Anti-influenza A Virus Effects and Mechanisms of Emodin and Its Analogs via Regulating PPARα/γ-AMPK-SIRT1 Pathway and Fatty Acid Metabolism. (9th September 2021) - Bei, Yufei; Tia, Boyu; Li, Yuze; Guo, Yingzhu; Deng, Shufei; Huang, Rouyu; Zeng, Huiling; Li, Rui; Wang, Ge-Fei; Dai, Jianping
Abstract : The peroxisome proliferator-activated receptor (PPAR) α / γ -adenosine 5 ′ -monophosphate- (AMP-) activated protein kinase- (AMPK-) sirtuin-1 (SIRT1) pathway and fatty acid metabolism are reported to be involved in influenza A virus (IAV) replication and IAV-pneumonia. Through a cell-based peroxisome proliferator responsive element- (PPRE-) driven luciferase bioassay, we have investigated 145 examples of traditional Chinese medicines (TCMs). Several TCMs, such as Polygonum cuspidatum, Rheum officinale Baillon, and Aloe vera var. Chinensis (Haw.) Berg., were found to possess high activity. We have further detected the anti-IAV activities of emodin (EMO) and its analogs, a group of common important compounds of these TCMs. The results showed that emodin and its several analogs possess excellent anti-IAV activities. The pharmacological tests showed that emodin significantly activated PPAR α / γ and AMPK, decreased fatty acid biosynthesis, and increased intracellular ATP levels. Pharmaceutical inhibitors, siRNAs for PPAR α / γ and AMPK α 1, and exogenous palmitate impaired the inhibition of emodin. The in vivo test also showed that emodin significantly protected mice from IAV infection and pneumonia. Pharmacological inhibitors for PPAR α / γ and AMPK signal and exogenous palmitate could partially counteract the effects of emodin in vivo. In conclusion, emodin and its analogs are a group of promising anti-IAV drug precursors, and the pharmacological mechanism of emodin is linked to its ability to regulate the PPAR α / γ -AMPK pathway and fatty acid metabolism.